Uncertain Material Parameter Extraction using FEKO Optimizations for Space Applications - McVay, John Anthony; Rai, Sandip; Avina, Isaac; Tran, Huu (2023 International Applied Computational Electromagnetics Society Symposium (ACES), 2023)
Spaceborne assets are subject to the harsh environments of outer space requiring the use of Multilayer Insulation (MLI) to provide the electronics inside the asset with a stable environment to operate. These assets are vulnerable in contested space and require some means of monitoring their surroundings. Most electronic payloads exploit the environmental stability underneath the MLI. These internal components would not be able to monitor the space outside of the asset. Sensing capabilities that can survive the harsh environments must be integrated to the asset's exterior. In this work, a Leaky-Wave Antenna (LWA) radar is designed and fabricated using bonded MLI materials. This allows the radar to be integrated onto the MLI. Uncertain material parameters, including material electrical permittivity and loss tangent, are extracted and estimated for bonded spaceborne MLI.